PENGARUH KOMUNIKASI TERHADAP KEBERHASILAN PELAYANAN SIDANG DI LINGKUNGAN SEKRETARIAT JENDERAL MPR RI - Suwarto, - (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2014)
The provision of public services is measured through information disclosure and how much interaction communication between the bureaucracy as a community service providers with service users. The purpose of writing is to investigate and analyze how much influence the communication to the success of the trial service in the Secretariat General of the MPR. This research was conducted by using descriptive analytic survey. The conclusion of this study are that: The communication has a positive and significant impact on the success of the trial service in the Secretariat General of the MPR. (2) The communication is woven by members of the working relationship aimed at improving the relationship between individuals and between work units or organizations and encourage morale. So it looks the importance of communication to increase the success of the trial service in the Secretariat General of the MPR.